Isi Piringku Dietary Meal Proportion Estimator Applications using SeeFood Image Segmentations - Fatahah Dwi Ridhani; Pritasari Pritasari; Dyah Retno Anggraini (Politeknik Kesehatan Kemenkes Jakarta II, 2021)
Isi Piringku atau My Meal Dish Content was a program initiated by the Indonesian ministry of health to promote a healthy daily lifestyle consisting of balanced dietary, enough hydration, active lifestyle, cleanliness and body weight control. The balanced diet meal was supposed to consist of ⅓ of carbohydrate intake, ⅓ of vegetable intake, ⅙ of fruit intake and ⅙ of protein intake every time. This introduces some difficulty that every meal must be measured to align with the dietary guidelines. This study targets estimating the meal diet proportion by its visual cues using smartphone application. While the actual meal content dietary division was weight based, for sake of simplicity the proportion in this study was estimated by each food area which roughly correlates to its volume. Using smartphone cameras in Android 9 Operating Systems and Tensorflow Lite Seefoods: Mobile Food Segmentation v1.0 module, an application was built to help users estimate their meal balances proportion. The original segmentation criterion was constructed using USDA dietary guidelines and it was reduced to only 4 food groups related to Isi Piringku criterion. Suggestion will be given regarding the segmentation result. The result was that the application was capable of estimating the meal diet proportion and giving suggestions based on the segmentation result. Although, the volume of the meal food groups estimated was still low on accuracy. This was correlated with the accuracy level of the segmentation module that was used. On average, the time needed to apply the segmentation process was around 2 to 3 seconds on a Snapdragon 835 device.